Pro-environmental messages in job advertisements and the intentions to apply—The mediating role of organizational Attractiveness - Pinto Coelho, Mafalda (2022)
: Environmental sustainability is a concept with increasing importance in the way organizations think and outline their cultures, practices, and business strategies to become more attractive. In this sense, the present study aims to understand whether organizations that publish job advertisements regarding sustainable culture and ecological concerns are perceived as more attractive and generate higher intentions to apply. A quantitative study was made with a sample comprising 443 participants. The results suggested that job advertisements with pro-environmental messages generate a higher organizational attractiveness. In addition, organizational attractiveness does not mediate the relationship between the type of advertisement (green vs. non-green) and intentions to apply. Additionally, the results suggested that individuals with greater individual environmental responsibility and intentions of pro-environmental behavior have a greater intention to apply, facing green job advertisements. The role of organizations in adopting green practices to attract and retain the best talent is also discussed, as well as suggestions for future studies.